Prospects of Vaccine in Leishmaniasis (Bangladesh Journal of Medical Microbiology, 2010)
The clinical manifestations of leishmaniasis depend on the interaction between the genetics of the parasite and the genetics of the host. However, in human infections, the host population is heterogeneous and the parasites are not clonal, and this makes it difficult to dissect out the relative contributions of the parasite and the host. The current data indicate that susceptibility to leishmaniasis is controlled by many genes, including TNF (tumor necrosis factor), MHC (major histocompatibility complex), NRAMP1 (natural resistance associated macrophage protein 1) and others of unknown function. Susceptibility, resistance, and disease patterns probably depend on complex interactions between these genes. However, despite the wealth of information regarding the genetics of the parasite and the experimental immunology of the disease, there is currently no licensed vaccine against Leishmania and control measures rely on chemotherapy to alleviate disease and on vector control to reduce transmission. A major vaccine development program aimed initially at cutaneous leishmaniasis is under way. Studies in animal models and humans have been evaluating the potential of genetically modified live attenuated vaccines, as well as a variety of recombinant antigens or the DNA encoding them. The availability, in the near future, of the DNA sequences of the entire human and Leishmania genomes will extend the vaccine program by mapping the host susceptibility genes to allow the vaccine to be targeted to the population most in need of protection. This review has focused on the factors elucidated for host and parasite governing disease outcome and also several of the Leishmania vaccination strategies employed to date.Bangladesh J Med Microbiol 2010; 03 (02): 40-46